Academic self efficiency and its relationship With The goal orientation types A field study on a sample of a class room teacher department at Tishreen University - Jdeed, Lubna (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The study aimed to discuss the relationship between Academic self efficiency and goal orientation types at a sample of teachers under training at Tishreen University, and knowing the level of academic self- efficiency, and the types of goal orientations which students have, beside exploring the differences between students’ academic self efficiency and goal orientation types according to gender , the sample was (384) students,(76) males and (308) females, by using the scale of the self- efficiency form in learning by (Barry j. Zimmerman & Anastasia Kitsantas), and the scale of goals orientation types by ( Elliot & Charch, 1997) after verifying of their reliability and validity in local environment. the results were as follows: -There is average level of academic self efficiency of teachers under training. -There is a positive relationship between academic self efficiency and mastery, performance orientation types, and there is a negative relationship with avoiding orientation . -The student adopt performance orientation type, then the mastery orientation at an average degrees, and a lower degree for avoiding orientation. -There are differences at academic self efficiency between males and females in favor of females. -There are differences between males and females only at performance orientation type in favor of females.